Progress of Time-Dependent Nuclear Reaction Theory - Iwata, Yoritaka (Bentham Science Publishers, 2019)
This book is a compilation of the latest theoretical methods for treating models in nuclear reactions. Initial chapters in this volume explain different aspects of time-dependent nuclear density functional theory, such as numerical calculations, density constrained models, multinucleon transfer reactions, and superfluid time dependent density functional theory. In addition, the volume also presents chapters covering other topics in nuclear physics, such as quantum molecular dynamics, cluster models in stable and unstable nuclei, chain structure theory in light nuclei, many-body systems and more. The volume is intended as a guidebook for graduate students and researchers to understand recent theories used in applied nuclear particle physics and astrology.